The 30 day MBA [electronic resource] : learn the essential top business school concepts, skills and language whilst keeping your job and your cash - Barrow, Colin (Kogan Page, 2009)
"The business world is full of conflicting theories and ideas on how organizations could or should work, and how they could be made to work better. However, the subject of business can be condensed down to 12 fundamental disciplines. These core disciplines make up the subject matter of an MBA programme and form the content of this book." "Incorporating case examples and links to online self-assessment tests, as well